1996
DOI: 10.1074/jbc.271.27.15891
|View full text |Cite
|
Sign up to set email alerts
|

Aging-dependent Functional Alterations of Mitochondrial DNA (mtDNA) from Human Fibroblasts Transferred into mtDNA-less Cells

Abstract: To investigate the role that aging-dependent accumulation of mitochondrial DNA (mtDNA) mutations plays in the senescence processes, mitochondria from fibroblasts of 21 normal human individuals between 20 weeks (fetal) and 103 years of age were introduced into human mtDNA-less ( o ) 206 cells by cytoplast ؋ o cell fusion, and 7-31 transformant clones were isolated from each fusion. A slight cell donor age-dependent decrease in growth rate was detected in the transformants. Using an O 2 consumption rate of 1 fmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
40
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(44 citation statements)
references
References 49 publications
3
40
1
Order By: Relevance
“…1). Therefore, the apparent discrepancy between the report of Laderman et al (12) and ours (11) could be due simply to a difference in the interpretation of observations.…”
Section: Discussioncontrasting
confidence: 53%
See 3 more Smart Citations
“…1). Therefore, the apparent discrepancy between the report of Laderman et al (12) and ours (11) could be due simply to a difference in the interpretation of observations.…”
Section: Discussioncontrasting
confidence: 53%
“…Recently, using an mtDNA transfer system similar to ours (11), i.e. mtDNA transfer from human skin fibroblasts to 0 human cells, Laderman et al (12) reported contradictory results, suggesting the presence of age-related heritable alterations in fibroblast mtDNA. However, the procedure for isolating cybrids by the transfer of fibroblast mtDNA to 0 cells is not appropriate for unambiguous determination of whether accumulation of mtDNA mutations is involved in age-related mitochondrial dysfunction, because during selection to exclude 0 cells using medium without uridine and/or pyruvate, cybrids expressing respiration deficiency due to accumulation of mtDNA mutations might also be eliminated preferentially, so that only cybrids with normal mitochondrial respiratory function are isolated.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…A similar relaxation of the copy number control, in this case produced by an inherited or somatic C150T mutation, may conceivably operate to accelerate mtDNA replication in centenarians and twins. It should be mentioned that a very significant decline with the donor's age in mtDNA content has been previously demonstrated in transformants constructed by transfer of mitochondria from fibroblasts of differently aged individuals into human mtDNA-less cells (24). An interesting possibility is that the somatic event(s) at or near position 150 leading to the appearance and͞or amplification of the C150T transition may be a part of a general remodeling of the mtDNA replication machinery, probably nuclearly controlled.…”
Section: Discussionmentioning
confidence: 99%